Synthesis of silver nanoparticles from coffee parasite leaf extract (Scurrulla ferruginea (Roxb. ex Jack) Danser) and potential activity as an antioxidant and anticancer - Destria Roza; Tico Guinessha Samosir; Sri Adelila Sari; Rini Selly (Pascasarjana Universitas Negeri Medan, 2024)
This study aim is to know the results of the synthesis of silver nanoparticles from quercetin and Scurrula ferruginea (Roxb. Ex Jack) danser as well as its potential as an antioxidant and anticancer. The solvent used in the maceration extraction method in this research is the polar solvent methanol. Isolation and purification of thick extract compounds from coffee parasite leaves were carried out using liquid vacuum chromatography (CVC) and gravity column chromatography (GCC) methods. Silver (Ag) nanoparticle is made with the stirrer method at a speed of 1500 rpm for 60 minutes at a temperature of 70o C. Silver nanoparticle solution was produced and then characterized using FTIR (Fourier Transform Infra Red) and PSA (Particles Size Analyzer). PSA results analysis using extract coffee parasite size 214 nm particles, whereas using flavonoid isolate quercetin confirmed size 29 nm. FTIR showed that there was a stretching vibration of the OH group at a wave number of 3229.25 cm-1, the C=O function at the wave number 1637.87 cm-1, and the CO functional group at the wave number 1016.31 cm-1. Antioxidant test using the DPPH method was carried out in silver nanoparticle solution using extract Scurrula ferruginea (Roxb. Ex Jack) danser and with quercetin obtained an IC50 value of around 115.4 and 114.9 this result describes as moderate level of antioxidants. Even though the nanoparticle anticancer test was very weak, overall, the synthesis of silver nanoparticles using flavonoid isolates was better than using extracts from coffee parasite leaves.